Estudo filológico de manuscritos de Luiz de Albuquerque de Mello Pereira e Cáceres - Almeida, Camila Lemos de (2013)
This work consists of philological, codicological and paleographic studies of manuscripts from the eighteenth century, between the years 1773 and 1789, period of the Governor Capitan-General, Luiz de Albuquerque de Mello Pereira e Cáceres. The corpus is composed by thirty-four documents named bands that refer to the Captaincy of Mato Grosso and Cuiabá, belonging to the collection of the Public Archives of Mato Grosso - APMT. The study of the corpus concentrated on the most relevant historical aspects of the colonial period of Mato Grosso concerning the political importance of Luiz de Albuquerque, followed by the facsimile and semi- diplomatic editions, aiming at the recovery and the transcription of historical documents, as well as the codicological and paleographic comments. The first addresses the study of the material used, the nature and origin of the paper, the composition of the colors and the paints, the dimension and composition of the notebooks, numeration, columns, margins, filigrees, particularities and content, and the second highlights the description and analysis of the graphic characters, typefaces, orthographic characteristics, brachygraphic and stigmeologic system. In the corpora under study the adjective and transcendent functions of the philological activity were considered. The analysis of the first attempts to deduce what is not in the text, such as an authorship, date and biography of the author and the second sees the text become an instrument that allows for the reconstitution of the social and cultural history of the people of Mato Grosso in a certain period. This corpus is exceedingly relevant to the rescue of the social history of the Portuguese and regional language and, also, contributes to the transmission and preservation of this cultural heritage. Having as a methodological theoretical-methodological basis of Azevedo Filho (1987), Spina (1994), Cambraia (2005), Andrade (2007), Santiago- Almeida (2009), among others.